Dynamic Phosphorylation of the Myocyte Enhancer Factor 2Cα1 Splice Variant Promotes Skeletal Muscle Regeneration and Hypertrophy. (28th September 2016) - Baruffaldi, Fiorenza; Montarras, Didier; Basile, Valentina; De Feo, Luca; Badodi, Sara; Ganassi, Massimo; Battini, Renata; Nicoletti, Carmine; Imbriano, Carol; Musarò, Antonio; Molinari, Susanna
Abstract : The transcription factor MEF2C (Myocyte Enhancer Factor 2C) plays an established role in the early steps of myogenic differentiation. However, the involvement of MEF2C in adult myogenesis and in muscle regeneration has not yet been systematically investigated. Alternative splicing of mammalian MEF2C transcripts gives rise to two mutually exclusive protein variants: MEF2Cα2 which exerts a positive control of myogenic differentiation, and MEF2Cα1, in which the α1 domain acts as trans-repressor of the MEF2C pro-differentiation activity itself. However, MEF2Cα1 variants are persistently expressed in differentiating cultured myocytes, suggesting a role in adult myogenesis. We found that overexpression of both MEF2Cα1/α2 proteins in a mouse model of muscle injury promotes muscle regeneration and hypertrophy, with each isoform promoting different stages of myogenesis. Besides the ability of MEF2Cα2 to increase differentiation, we found that overexpressed MEF2Cα1 enhances both proliferation and differentiation of primary myoblasts, and activates the AKT/mTOR/S6K anabolic signaling pathway in newly formed myofibers. The multiple activities of MEF2Cα1 are modulated by phosphorylation of Ser98 and Ser110, two amino acid residues located in the α1 domain of MEF2Cα1. These specific phosphorylations allow the interaction of MEF2Cα1 with the peptidyl-prolyl isomerase PIN1, a regulator of MEF2C functions. Overall, in this study we established a novel regulatory mechanism in which the expression and the phosphorylation of MEF2Cα1 are critically required to sustain the adult myogenesis. The described molecular mechanism will represent a new potential target for the development of therapeutical strategies to treat muscle-wasting diseases.